THU0223 Genetics of behçet's disease in sardinia: two distinct extended hla haplotypes harbor the B*51 allele in normal population and in patients. (23rd January 2014) - Piga, M.; Paladini, F.; Lai, S.; Passiu, G.; Carcassi, C.; Sorrentino, R.; Mathieu, A.
Abstract : Background: Several observations suggest that genes other than HLA-B*51 might be implicated in BD susceptibility and pathogenesis. In particular, as a consequence of the strong linkage disequilibrium characterizing the MHC region, it cannot be ruled out that HLA-B*51 is included in haplotypes with other functional genes partly responsible of genetic susceptibility to BD. The distribution of HLA alleles in Sardinian natives is characterized by highly preserved haplotypes. Objectives: To define the contribution of HLA genes and extended HLA haplotypes conferring susceptibility to Behçet's Disease (BD), through analysis of Sardinian subjects. Methods: Forty-five unrelated Sardinian patients with BD, diagnosed according to the ISG criteria, 45 HLA-B*51 positive and 185 unselected healthy controls were enrolled in the study. DNA samples were typed for HLA class I and class II alleles and genotyped for microsatellites (MICA-TM) and single-nucleotide polymorphisms (rs1264457 HLA–E; rs2281820 motilin; rs1799724 at -857, rs361525 at -238 TNF-alpha) spanning the HLA region. Statistical analysis was carried out using Chi-square test with Yates' correction or Fischer's exact test. The strength of association was estimated by calculating the Odds Ratio (OR) with 95% Confidence Interval (95% CI). A value of p<0.05 was considered statistically significant where Bonferroni's correction was applied. The LD between pairs of loci was calculated performing a likelihood-ratio test, whose empirical distribution is obtained by a permutation procedure using the statistical software Arlequin (version 3.11, Bern, Switzerland). The significance (p<0.01) of the observed likelihood ratio is found by computing the null distribution of this ratio under the hypothesis of LD, using a permutation procedure. All markers were in Hardy-Weinberg equilibrium. Maximum-likelihood haplotype frequencies and their distribution were estimated using an Expectation-Maximization algorithm and polymorphic alleles within each investigated HLA locus were constructed into extended haplotypes. Results: The HLA-B*51 allele, in particular the B*51:01, was the only allele conferring susceptibility to BD (pc=0.0042; OR =4.4; 95% CI =2.0 to 9.6), among those investigated. The B*51 allele was more frequently carried by a haplotype (A2; Cw2; B*51:01; DRB1*11; DQA1*05; DQB1*03) that reached its highest frequency in patients with BD.Linkage disequilibrium analysis showed the existence of a B*51 haplotype (A2; Cw2; B*51:01; DRB1*04; DQA1*03; DQB1*03) not associated with susceptibility to the disease (figure 1). None of the investigated microsatellites and SNPs showed a different distribution in B*51 haplotypes characterizing healthy controls and BD patients. Conclusions: We confirmed that B*51 is the major genetic susceptibility factor to BD and we described a significant low frequency of A2; Cw2; B*51:01; DRB1*04; DQA1*03; DQB1*03 haplotype in our patients. It might be speculated this haplotype lacks a hypothetical co-susceptibility genetic factor to BD in Sardinian natives. Disclosure of Interest: None Declared